Perception of Immigrants in Europe: A Multilevel Assessment of Macrolevel Conditions. (4th November 2020) - Boateng, Francis D.; McCann, Wesley S.; Chenane, Joselyne L.; Pryce, Daniel K.
Abstract : Objective: In recent times, immigration has been a controversial topic. Discussions about immigration have become common household conversation. The primary objective of the current study is to explore the dynamics of native‐born citizens' attitudes toward immigrants and examine the potential influence of macro‐level conditions. Methods: The current study employed multi‐level techniques to examine macro‐level effects on attitudes toward immigrants across 22 European countries. Specifically, three Hierarchical Linear Models were conducted to achieve the study's stated objective. Results: The Hierarchical Linear Modeling (HLM) analyses revealed that a country's level of economic development as measured by changes in gross domestic product (GDP) and education significantly influenced native‐born citizens' views about immigrants. Moreover, the number of immigrants (per 1, 000 residents) and crime rates determine whether native‐born Europeans will view foreigners positively or negatively. Nevertheless, a country's unemployment rate had no significant effect on perceptions of immigrants. Several individual‐level characteristics were found to predict perceptions of immigrants among native‐born Europeans. Conclusion: Results from this endeavor provide insights for addressing common misconceptions about immigration and also help in understanding, from empirical standpoint, how native‐born citizens form their views about immigrants.